Identifying students of concern. Primary school teachers’ reflections on assessing students’ general school functioning based on the concept of typicality - Ekornes, Stine; Holen, Solveig; Ingul, Jo Magne; Neumer, Simon-Peter; Adolfsen, Frode; Bania, Elisabeth Valmyr (Frontiers in Psychology, 2025)
IntroductionThe present paper explores how Norwegian primary school teachers’ reason and reflect when assessing students’ general school functioning in Teacher’s Report Form (TRF), where teachers are asked to compare students of concern with what is perceived as a typical student at the same age, regarding work effort, behavior, learning capacity and mood.MethodsThe teachers in the sample (n = 7) had recently filled out the TRF as part of their participation in The Echo Study, utilizing the cognitive behavior therapy program Emotion for sad and anxious children.ResultsThe results show that teachers base their assessments much on person-relative, rather than group- or age relative comparisons, e.g., what is normal for the individual student. It is also identified that a safe psychosocial environment where students feel confident speaking up and exploring new ideas, is recognized as essential or optimal school functioning and attendance. This is especially important for children experiencing sadness or anxiety.DiscussionBy understanding more of how teachers reason when assessing students’ general school functioning, we can aid their efforts to identify students of concern. Poor school functioning is related to school absenteeism, and teachers are front-line professionals to observe early warning signs based on their understanding of whether a student’s behavior lies within or outside the range of typical functioning.